Impacto das culturas da cana-de-açúcar e do abacaxi nas propriedades hidrodinâmicas do solo da Bacia do Rio Gramame-PB. - Sales, Érika Gonçalves (2013)
In this study we determined the hydraulic conductivity and retention in soils of river basin Gramame, by comparison with the soils of the areas native atlantic, using the method Beerkan. To apply this method it was necessary to carry out tests on 36 points basin. Beerkan The method is based on field experiments, using static and dynamic properties of the soil, as the grading curve and the curve of water infiltration into the soil, where tests are conducted to determine infiltration simplified hydrodynamic parameters. In Beerkan curves water retention in the soil θ (h) and hydraulic conductivity K (θ) can be described by five parameters, two and three way of standardization. The shape parameters are obtained from the distribution curve of the particle sizes F (D) and porosity, whereas the normalization parameters are determined from experiments infiltration. The results obtained in the cultivation areas were compared with the results of the atlantic forest. It was found that the central area of the basin showed higher responses related to the hydraulic conductivity, especially the higher levels located in the remaining areas of rainforest. Of the total points, 18 were discarded because the curves did not obey a specific pattern does not occur to stabilize the blade infiltrated. It was concluded that even a portion of the soil under vegetation cover and provided results similar to those of cultivated areas, most of the points located in the area that comprises the largest conductivities are points in the area of rainforest. Therefore, it is perceived by some activity impacting crops to soil, situation smaller representation in the remaining areas of rainforest in order that the highest values of hydraulic conductivity are in these areas due to the protective effect by vegetation.